Magnetic bead-based adsorption strategy for exosome isolation - Jiawei, Sun; Zhi, Chen; Kewei, Tian; Xiaoping, Li (Frontiers in Bioengineering and Biotechnology, 2022)
Exosomes, one type of extracellular vesicle (EV) secreted by cells, participate in intercellular communication and other biological processes as carriers of lipids, functional proteins, mRNAs, miRNAs, lncRNAs, and DNA fragments. Their presence in biofluids makes them attractive candidates as innovative clinical diagnostic tools. However, conventional isolation and analysis of high-purity exosomes in clinical application is challenging, with traditional methods facing a number of shortcomings, including low yield or purity, long periods of processing, high cost and difficulties in standardization. In this review, we provide an overview of commonly used exosome isolation approaches with a focus on magnetic bead-based capture, an ideal methodology with high purity and integrality of exosomes. The current challenges on exosome isolation methods are also described to highlight areas for future research and development.